1998
DOI: 10.1021/jf9805754
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Isothiocyanates Produced by Glucosinolates in Brassicaceae Species to Black Vine Weevil Eggs

Abstract: Control of the black vine weevil, Otiorhynchus sulcatus (F.), with allelochemicals produced from glucosinolates may be possible; however, plant-derived isothiocyanates are not readily available for bioassays. Our objective was to predict the toxicity of plant-derived isothiocyanates using a model developed with commercially available compounds. Contact toxicities of 12 organic isothiocyanates were determined by dipping black vine weevil eggs into isothiocyanate solutions. Quantitative relationships between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 30 publications
4
56
0
3
Order By: Relevance
“…Thirdly, the aromatic GSL are more lipophilic, which increases membrane permeability, thus contributing to the higher contact toxicity often reported for the aromatic ITCs. Moreover, the ethyl bridge linking the phenyl group with the functional ITC may act to hold the active ITC free of the soil organic matrix allowing better contact with soil organisms (Potter et al 1998), a structural feature absent from benzyl ITC which is less prevalent in roots (Borek et al 1998). Even though a recent lab study showed that the volatile insecticidal activity of 2PE-ITC may be mitigated by the soil environment more than that of other ITCs (Matthiessen and Shackleton 2005), many other studies showed that 2-PE ITC was among the most toxic upon direct contact to a range of soil-borne organisms, including soil insects (Borek et al 1995(Borek et al , 1998, pathogenic fungi , phytophagous root nematodes (Potter et al 1999(Potter et al , 2000 and wheat seeds (Bialy et al 1990).…”
Section: Feeny and Rosenberry (1982)mentioning
confidence: 99%
“…Thirdly, the aromatic GSL are more lipophilic, which increases membrane permeability, thus contributing to the higher contact toxicity often reported for the aromatic ITCs. Moreover, the ethyl bridge linking the phenyl group with the functional ITC may act to hold the active ITC free of the soil organic matrix allowing better contact with soil organisms (Potter et al 1998), a structural feature absent from benzyl ITC which is less prevalent in roots (Borek et al 1998). Even though a recent lab study showed that the volatile insecticidal activity of 2PE-ITC may be mitigated by the soil environment more than that of other ITCs (Matthiessen and Shackleton 2005), many other studies showed that 2-PE ITC was among the most toxic upon direct contact to a range of soil-borne organisms, including soil insects (Borek et al 1995(Borek et al , 1998, pathogenic fungi , phytophagous root nematodes (Potter et al 1999(Potter et al , 2000 and wheat seeds (Bialy et al 1990).…”
Section: Feeny and Rosenberry (1982)mentioning
confidence: 99%
“…Variation in glucosinolate hydrolysis structure has been correlated with plant resistance against herbivores (Chew, 1988;Borek et al, 1998;Halkier, 1999;Jander et al, 2001;Lambrix et al, 2001). The ESP and ESM1 loci were first identified as QTL for nitrile formation, resistance to T. ni (cabbage looper), and taste preference of T. ni (Jander et al, 2001;Lambrix et al, 2001).…”
Section: Investigation Of Esm1 Effects On Insect Herbivorymentioning
confidence: 99%
“…This occurs when endogenous myrosinase is released during the disruption of plant cells by harvesting, processing, or mastication. Glucosinolate breakdown products play prominent roles in plant-herbivore and plant-pathogen interactions (Chew, 1988;Borek et al, 1998;Halkier, 1999;Lambrix et al, 2001) and have potential antiulcer and anticarcinogenic properties (Zhang et al, 1994;Hecht, 2000). Hydrolysis of a single glucosinolate can produce a nitrile, an isothiocyanate, or a thiocyanate, with the final structure controlling the bioactivity (Lambrix et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of long-chain aliphatic glucosinolates increased after MeJA treatment. This could be part of the response to make the plant more resistant to pathogens as the toxicity of the glucosinolate breakdown products in general increases with increasing side-chain length (Borek et al, 1998). MeJA has not previously been identified as an inducer of long-chain aliphatic glucosinolates.…”
Section: Hormonal Treatments Of Wild-type Arabidopsismentioning
confidence: 99%